1979
DOI: 10.1128/aem.38.1.84-89.1979
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Biodegradation of Eleven Aromatic Compounds to Methane

Abstract: A range of 11 simple aromatic lignin derivatives are biodegradable to methane and carbon dioxide under strict anaerobic conditions. A serum-bottle modification of the Hungate technique for growing anaerobes was used for methanogenic enrichments on vanillin, vanillic acid, ferulic acid, cinnamic acid, benzoic acid, catechol, protocatechuic acid, phenol, p-hydroxybenzoic acid, syringic acid, and syringaldehyde. Microbial populations acclimated to a particular aromatic substrate can be simultaneously acclimated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
2
3

Year Published

1985
1985
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(88 citation statements)
references
References 20 publications
1
82
2
3
Order By: Relevance
“…The amended nitrate medium (ANM) used for culture enrichment was prepared according to Taylor et al [5] with the following modifications (per 1): KNO 3, 3.0 g; FeSO 4-7H20, 25.0 mg; CuSO4.5H20, 0.3 mg; NiCI2.6H20, 0.8 mg; yeast extract (Difco Detroit, MI), 10.0 mg; trace mineral solution [13], 15.0 ml and distilled water added to volume. The medium (pH 6.9) was dispensed under argon gas in 100 ml aliquots to argon-gassed serum bottles with butyl rubber stoppers (Bellco Glass, Vineland, N J) and autoclaved.…”
Section: Media and Solutionsmentioning
confidence: 99%
“…The amended nitrate medium (ANM) used for culture enrichment was prepared according to Taylor et al [5] with the following modifications (per 1): KNO 3, 3.0 g; FeSO 4-7H20, 25.0 mg; CuSO4.5H20, 0.3 mg; NiCI2.6H20, 0.8 mg; yeast extract (Difco Detroit, MI), 10.0 mg; trace mineral solution [13], 15.0 ml and distilled water added to volume. The medium (pH 6.9) was dispensed under argon gas in 100 ml aliquots to argon-gassed serum bottles with butyl rubber stoppers (Bellco Glass, Vineland, N J) and autoclaved.…”
Section: Media and Solutionsmentioning
confidence: 99%
“…It has been shown that lignin-derived monoaromatic alcohols and acids can be completely degraded under methanogenic conditions [1][2][3][4][5]. The populations capable of such transformations are complex communities consisting of strictly anaerobic [6] and facultatively anaerobic fermentative bacteria [7,8], methanogens [5], and possibly also hydrogen-producing acetogens as an intermediary link between the two groups.…”
Section: Introductionmentioning
confidence: 99%
“…These substrates were therefore often considered recalcitrant in the absence of molecular oxygen [2], and catechol especially was found to be quite stable under anaerobic conditions [3,4]. Nonetheless, complete methanogenic degradation of phenolic and other aromatic compounds such as lignin monomers has been reported [5][6][7]. Methanogenic degradation of benzoate depends on a syntrophic co-operation of fermentative and hydrogen-oxidizing methanogenic bacteria [8,9], whereas trihydroxybenzoates and trihydroxybenzenes were fermented to acetate in pure culture [10].…”
Section: Introductionmentioning
confidence: 99%